Data Compression for Multiple Scan Chains Using Dictionaries with Corrections - Hellebrand, Sybille; Wuertenberger, Armin; S. Tautermann, Christofer
Keywords: WORKSHOP

Effiziente Videoproduktionsprozesse fuer komponentenbasierte E-Learning Inhalte - Trier, Matthias; Müller, Claudia; Herzog, Michael (Proceedings Potsdamer Multimedia Konferenz 2004)

Konzepte für die Videoproduktion in virtuellen Lernszenarien Beitrag zum Kollegiatentag 2004 des SVKB - Herzog, Michael A.; Trier, Matthias

IT-Supported Monitoring and Analysis of Social Networks in Virtual Knowledge Communities - Trier, Matthias (Proceedings Sunbelt XXIV Conference, Portoroz, Slovene, INSNA Association, 2004)

Measuring Brokering Activity - a novel measure for dynamic network evolution - Trier, Matthias; Bobrik, A. (Proceedings Sunbelt XXVII Conference, Corfu, Greece, INSNA Association, 2007.)

Distributed maintenance of resource reservation paths in multihop 802.11 networks - Carlson, Emma; Bettstetter, Christian; Karl, Holger; Prehofer, Christian; Wolisz, Adam (Vehicular Technology Conference, 2004. VTC2004-Fall. 2004 IEEE 60th)

On the effect of inband signaling and realistic channel knowledge on dynamic OFDM-FDMA systems - Gross, James; Karl, Holger; Wolisz, Adam (European Wireless 2004)

A MAC protocol for wireless sensor networks with multiple selectable, fixed-orientation antennas - Kubisch, Martin; Karl, Holger; Wolisz, Adam (Frequenz)

Measurements of edge-uncolorability - Steffen, Eckhard (Discrete Mathematics)

Independent Sets and 2-factors in edge-chromatic critical graphs - Grünewald, Stefan; Steffen, Eckhard (J. Graph Theory)

Throughput optimization of dynamic OFDM-FDMA systems with inband signaling - Gross, James; Karl, Holger; Wolisz, Adam (2nd International Symposium on Modeling and Optimization in Mobile, Ad Hoc, and Wireless Networks 2004 (WiOpt 2004))

A Runtime Environment for Reconfigurable Hardware Operating Systems - Walder, Herbert; Platzner, Marco (Proceedings of the 14th International Conference on Field Programmable Logic and Applications (FPL))

XF-BOARD: A Prototyping Platform for Reconfigurable Hardware Operating Systems - Walder, Hebert; Nobs, Samuel; Platzner, Marco (Proceedings of the 4th International Conference on Engineering of Reconfigurable Systems and Algorithms (ERSA))

Efficient Execution of Process Networks on a Reconfigurable Hardware Virtual Machine - Dyer, Matthias; Platzner, Marco; Thiele, Lothar (Proceedings 12th Annual IEEE Symposium on Field-Programmable Custom Computing Machines (FCCM))

Aus dem Italienischen ins Deutsche: F. D’Agostini, Che cosa significa essere una donna? Le basi ontologiche della differenza di genere tra analisi concettuale e teoria politica

,Aber vielleicht kommt noch eine Zeit, wo auch meine Arbeiten wieder entdeckt und gelesen werde‘: Die gescheiterte Karriere des Ernst Zermelo - Peckhaus, Volker (Mathematik im Fluß der Zeit. Tagung zur Geschichte der Mathematik in Attendorn/Neu-Listernohl (28.5. bis 1.6.2003))

Otto Friedrich Gruppe und die Logische Frage - Peckhaus, Volker (Otto Friedrich Gruppe 1804–1876. Philosoph, Dichter, Philologe)
Rezension: Journal of the History of Philosophy 43.3 (2005), 367–369 (H.J. Cloeren).

Paradoxes in Göttingen - Peckhaus, Volker (One Hundred Years of Russell's Paradox. Mathematics, Logic, Philosophy)

Garantiert Widerspruchsfreiheit Existenz? - Peckhaus, Volker (Was folgt? Themen zu Wessel)

Dignaga’s Logic of Invention - Peckhaus, Volker (History of the Mathematical Sciences)
Rezension: Zbl. Math. 1049.01008 (A. C. Lewis).